Digital Financial Recording Adoption among Traditional Market Traders: Evidence from DTC Wonokromo Indonesia - Devi Maya Sofa (Institut Agama Islam Negeri Kerinci, 2026)
Purpose: This study aims to explore the adoption of digital financial recording systems among traders in traditional markets by analysing the perspectives, readiness, perceived benefits, and challenges faced by merchants at DTC Wonokromo, Surabaya. Design/Methodology/Approach: This research employs a qualitative approach using a triangulation method through in-depth interviews, direct observation, and document analysis. The study involved merchants from seven different business categories to capture diverse experiences in adopting digital bookkeeping practices. Data were analysed using thematic analysis to identify patterns related to adoption behaviour and digital readiness. Findings: The findings reveal significant variations in the level of understanding and adoption of digital financial recording systems among traders. Merchants with undergraduate educational backgrounds aged between 45–55 years demonstrated higher levels of adoption, while younger employees aged 24–35 years showed stronger technical adaptability. Businesses in the electronics & accessories and jewellery sectors exhibited the highest adoption levels. The main perceived benefits include time efficiency, improved recording accuracy, easier access to financial history, and better inventory management. However, several challenges remain, including infrastructure limitations, employee resistance to change, implementation costs, data security concerns, and limited technical support. Overall, most traders demonstrated moderate to high readiness to transition toward digital accounting practices. Research Implications: This study contributes to the literature on digital accounting adoption among MSMEs, particularly in traditional market contexts in developing countries. The findings highlight the importance of digital literacy support, infrastructure readiness, and change management strategies to accelerate digital financial transformation among small traders. The results also provide practical insights for policymakers and market authorities in designing targeted digitalization programs for MSMEs.